EXTRACURRICULAR QUALITY MANAGEMENT “TATANEN DI BALE ATIKAN” IN DEVELOPING ENVIRONMENTAL LOVE CHARACTERS IN ELEMENTARY SCHOOLS - Nuryani Apriyanti; Undang Ruslan Wahyudin; Saepul Ma’mun (Jurnal Cakrawala Pendas, 2025)
This study aims to analyze the quality management of Agriculture-based extracurricular quality in Balé Atikan (TdBA) in fostering the character of love for the environment at SDN Ekologi Kahuripan Padjadjaran, Purwakarta. Tatanen di Bale Atikan (TdBA) is an environment-based character education program developed by the Purwakarta Regency Government which aims to instill the values of love for nature through agricultural practices, waste management, and environmental conservation in educational units which are implemented, one of which is through extracurricular activities. A qualitative approach with a case study method is used to understand in depth the implementation of the program. Primary data was obtained through in-depth interviews, participatory observation, and documentation, while secondary data came from school policies and Regent Regulation No. 103 of 2021. Miles and Huberman's interactive data analysis was used by triangulating sources to ensure data validity. The results of the study show that the TdBA program has been quality-based, with the implementation of the PDCA (Plan-Do-Check-Act) cycle in planning, implementation, evaluation, and follow-up. Key challenges include limited resources and continuity of practice at home. The proposed solutions are integration with the curriculum, external collaboration, and strengthening community involvement, so that the program can become a national model of sustainable ecology-based education. These findings make a significant contribution to the development of an adaptive, participatory, and sustainable ecology-based national education policy, and can be used as a model for the implementation of environmental education in basic education units in various regions.